Impact of SiO2 content on the hydrogen based direct reduction performance of high-grade hematite pellets - Bohua Li; Deqing Zhu; Zhengqi Guo; Jian Pan; Congcong Yang; Siwei Li (Journal of Materials Research and Technology)
The gangue composition is one of the key factors influencing the reduction behavior of iron ore pellets, particularly the SiO2 content, which exerts a pronounced effect on the reduction performance of acidic pellets under hydrogen-rich atmospheres. In this study, high-grade hematite oxidized fired pellets with a basicity (CaO/SiO2) of 0.3 were prepared, and the SiO2 content was systematically varied from 1.0 % to 4.0 %. Reduction experiments were conducted under a simulated hydrogen-rich gas atmosphere, representative of the Midrex shaft furnace process. The results show that with increasing SiO2 content, the internal structure of the fired pellets becomes more compact, resulting in a decline in both the reduction rate and the metallization degree –from 98.88 % to 95.01 %. At the same time, the reduction swelling index significantly decreases from 21.56 % to 7.26 %, and the clustering index drops markedly from 19.56 % to 8.56 %. A moderate increase in SiO2 improves reduction disintegration resistance and suppresses carbon deposition. However, when SiO2 content reaches 4.0 %, a slight increase in reduction pulverization is observed. Mechanistic analysis reveals that a moderate increase in SiO2 content contributes to enhancing the structural stability of fired pellets, suppressing reduction swelling and clustering tendency, and thereby optimizing the overall reduction behavior. However, an excessive SiO2 content leads to increased slag phase formation, which hinders the reduction process, resulting in a lower metallization degree and aggravated reduction disintegration. This study provides a theoretical basis for the preparation and performance optimization of high-quality fired pellets suitable for hydrogen-based shaft furnace direct reduction processes.